2018
DOI: 10.1146/annurev-virology-092917-043515
|View full text |Cite
|
Sign up to set email alerts
|

Quis Custodiet Ipsos Custodes? Regulation of Cell-Mediated Immune Responses Following Viral Lung Infections

Abstract: Viral lung infections are leading causes of morbidity and mortality. Effective immune responses to these infections require precise immune regulation to preserve lung function after viral clearance. One component of airway pathophysiology and lung injury associated with acute respiratory virus infection is effector T cells, yet these are the primary cells required for viral clearance. Accordingly, multiple immune mechanisms exist to regulate effector T cells, limiting immunopathology while permitting clearance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 131 publications
0
22
0
Order By: Relevance
“…Journal Pre-proof J o u r n a l P r e -p r o o f 13 by killing the infected epithelial cells, and cytotoxic CD8+ T cells produce and release pro-inflammatory cytokines which induce cell apoptosis [46]. Both the pathogen (CoV) and cell apoptosis trigger and amplify the immune response.…”
Section: When Virus Is Inhaled and Infects Respiratory Epithelial Celmentioning
confidence: 99%
“…Journal Pre-proof J o u r n a l P r e -p r o o f 13 by killing the infected epithelial cells, and cytotoxic CD8+ T cells produce and release pro-inflammatory cytokines which induce cell apoptosis [46]. Both the pathogen (CoV) and cell apoptosis trigger and amplify the immune response.…”
Section: When Virus Is Inhaled and Infects Respiratory Epithelial Celmentioning
confidence: 99%
“…From the moment the virus is inhaled and infects the epithelial cells of the respiratory tract, dendritic cells phagocytose the virus and present antigens to T cells. The resultant effector T cells function by killing the infected epithelial cells, and cytotoxic CD8+ T cells produce and release pro-inflammatory cytokines, which induce cell apoptosis [48]. Both the pathogen (CoV) and cell apoptosis trigger and amplify the immune response.…”
Section: Melatonin and Immunomodulationmentioning
confidence: 99%
“…NKT cells embody a mixed population of T cells that possess killing properties of both NK and T cells and form a bridge between the innate and adaptive immune system. During viral infections, NKT cells exert effector functions but also regulate immune responses in order to limit lung inflammation [41]. Interestingly, a recent study by Gaya et al showed that NKT cells promote B cell immunity during viral infections via the release of IL-4 [143].…”
Section: Natural Killer Cells (Nks)mentioning
confidence: 99%
“…Virus-specific CD8+ T cells can selectively eliminate infected cells. Following peak expansion, the CD8+ T cells numbers shrink and a memory population of virus-specific CD8+ T cells remains in the lungs [41]. hMPV infection results in the accumulation of hMPV-specific cytotoxic and IFN-γ positive effector cells in both the airways and lungs seven days post infection.…”
Section: Cd8+ T Cellsmentioning
confidence: 99%
See 1 more Smart Citation